Marketing 6.0: The future in immersive - Kotler, Philip; Kartajaya, Hermawan; Setiawan, Iwan (New Delhi Wiley India Pvt. Ltd., 2025)
Rediscover the fundamentals of marketing along with the rise of metamarketing from the best in the businessIn Marketing 6.0, the celebrated promoter of the (3z(BFour P$1 (Bs of Marketing,(3y (BPhilip Kotler, explains how marketers can use technology to address customers$1 (Bneeds and make a difference in the world. In a new age of metamarketing, this book provides marketers with a way to integrate technological and business model evolution with the dramatic shifts in consumer behavior that have happened in the last decade. s